International relations
International Relations is an explicitly pluralist peer-reviewed journal, favouring variety in both subject-matter and method. IR welcomes articles from all perspectives and on all subjects pertaining to international relations including law, economics, ethics, strategy, philosophy, culture, and the environment, in addition to more mainstream conceptual work and policy analysis.